Validation of Analysis Methods for Phosphorus in Chicken Meat and Fresh Cow's Milk Using Microwave Destruction and Spectrophotometry Microplate UV-VIS - Ikhwan Hadianto; Siska Devi Kusumawati; Nurlatifah; Muhammad Rio Rafif; Rina Ispitasari (Animal Science Study Program, Faculty of Agriculture, Science and Health, Universitas Timor, 2025)
Phosphorus content in animal-derived foods is an important indicator of nutritional value and food safety. This study validated a method for phosphorus analysis in chicken meat and fresh cow’s milk using wet digestion based on microwave digestion and microplate UV-Vis spectrophotometry with the principle of molybdenum blue complex formation by ascorbic acid at a wavelength of 880 nm. Method performance was evaluated according to ISO/IEC 17025:2017. The validation parameters included linearity and linear range, sensitivity comprising the limit of detection (LOD) and limit of quantification (LOQ), precision comprising repeatability and intermediate precision, as well as accuracy. The calibration curve showed good linearity within the range of 2–12 ppm (r² = 0.998). The LOD and LOQ values were 0.29 and 0.97 mg/L for chicken meat, and 0.17 and 0.57 mg/L for cow’s milk, respectively. Precision testing resulted in repeatability and intermediate precision RSDs of 2.00% and 2.18% for chicken meat, and 2.62% and 2.14% for cow’s milk. Accuracy, determined by recovery analysis, showed values of 97.14% for chicken meat and 103.15% for cow’s milk. These results demonstrate that the validated method meets the acceptance criteria of ISO/IEC 17025. The method provides acceptable linearity, sensitivity, precision, and accuracy, and can be applied for routine phosphorus analysis in meat and milk matrices. Keywords: Phosphorus, chicken meat, cow’s milk, method validation, UV-Vis spectrophotometry